Determinants and Consequences of Land Sales Market Participation : Panel Evidence from India - Deininger, Klaus (2012)
Although opinions on impacts of land market transfers are sharply divided, few studies explore welfare- and productivity-impact of land sales markets over a long time horizon and national scale. A panel spanning almost 20 years, together with an indicator of climatic (rainfall) shocks, allows us to assess factors underlying market-mediated land (sale and purchase) transactions and their impact on productivity and equity. Economic growth emerges as a key driver of such markets although shocks, their effect mitigated by bank presence, also increased market activity. Land sales improved productivity and helped purchasers, many of them formerly landless, to accumulate non-land assets and enhance their welfare.